Enhancing bioelectricity generation through co-cultivation of bacteria consortium and microalgae in photosynthetic microbial fuel cell - Chaijak, Pimprapa; Kongthong, Alisa (Communications in Science and Technology, 2024)
This study investigates the effect of microbial configuration on the electrochemical performance of photosynthetic microbial fuel cells (PMFCs). The PMFC configuration incorporating both bacteria and microalgae exhibited the highest open-circuit voltage (OCV) of 397.95 ± 31.53 mV, significantly higher than that of the OCVs obtained in the sterile control (C1) and the microalgae-only configuration (C2), which were 32.47 ± 22.43 mV and 284.59 ± 12.63 mV, respectively. Furthermore, the PMFC containing only microalgae achieved a current density (CD) of 20.96 ± 0.18 mA/m³ and a power density (PD) of 0.40 ± 0.01 mW/m³ under room temperature conditions. Notably, the combined bacteria and microalgae configuration demonstrated a substantial performance improvement, yielding a significantly higher CD of 49.33 ± 0.36 mA/m³ and PD of 0.78 ± 0.01 mW/m³ at room temperature. This configuration also achieved a maximum decolorization of 93.57 ± 0.10% with a corresponding algal biomass recovery of 134.90 ± 2.69 mg/L. These findings highlighted the critical role of microbial composition in PMFC performance. The combination of bacteria and microalgae yielded superior results compared to other configurations under the investigated conditions.